A gyermekkori (CHEXI) és a felnőttkori (ADEXI) végrehajtó funkció kérdőívek magyar nyelvre történő adaptációja - Józsa Gabriella (Magyar pedagógia : a Magyar Tudományos Akadémia Pedagógiai Bizottságának folyóirata, 2020)
This paper describes the Hungarian adaptation of the Childhood Executive Functioning Inventory (CHEXI) and the Adult Executive Functioning Inventory (ADEXI). Both instruments were originally developed by Swedish researchers, but today, a number of adaptations exist. These adaptations have been used in several studies abroad. With CHEXI, teachers and parents rate the executive function of children aged 4‒12 years. ADEXI is a selfreport instrument which is suitable for use above the age of 12. Both instruments consist of five-point Likert items. The Hungarian adaptations were created in accordance with the guidelines of the International Test Commission. The first step of the adaptation process was translation, it was then followed by back translation, review, small-scale study, and finally another round of review. The large-scale data collection took place after all these steps. 229 preschool teachers and 166 parents filled out CHEXI to rate preschool students. As for the school-age sample, CHEXI was filled out by 166 teachers and 357 parents, while ADEXI was filled out by 283 students. Factor validity of the scales was confirmed in all sub-samples. The KMO value was found to be above 0.9 for CHEXI and 0.88 for ADEXI. Reliability values were also found to be high, the lowest Cronbach’s α for CHEXI sub-scales was 0.87. Reliability values for ADEXI were slightly lower but still appropriate: they ranged between 0.65 and 0.86. According to the results, the Hungarian adaptations demonstrated good psychometric properties. As a result of the adaptation, a new instrument was created for the Hungarian research community. The questionnaires are suitable for use in international comparison studies, and classroom practice may also find it beneficial. The primary significance of this study is given by the fact that these are the first instruments that are available for the study of the executive function in Hungarian.